Ethnicity and insurance status predict metastatic disease presentation in prostate, breast, and non‐small cell lung cancer. (8th June 2020) - Aghdam, Nima; McGunigal, Mary; Wang, Haijun; Repka, Michael C.; Mete, Mihriye; Fernandez, Stephen; Dash, Chiranjeev; Al‐Refaie, Waddah B.; Unger, Keith R.
Abstract: Background: Ethnicity and insurance status have been shown to impact odds of presenting with metastatic cancer, however, the interaction of these two predictors is not well understood. We evaluate the difference in odds of presenting with metastatic disease in minorities compared to white patients despite access to the same insurance across three common cancer types. Methods: Using the National Cancer Database, a multilevel logistic regression model that estimated the odds of metastatic disease was fit, adjusting for covariates including year of diagnosis, ethnicity, insurance, income, and region. We included adults diagnosed with metastatic prostate, non–small cell lung cancer (NSCLC), and breast cancer from 2004 to 2015. Results: The study cohort consisted of 1 191 241 prostate cancer (PCa), 1 310 986 breast cancer (BCa), and 1 183 029 NSCLC patients. Private insurance was the most protective factor against metastatic presentation. Odds of presenting with metastatic disease were 0.190 [95% CI, 0.182‐0.198], 0.616 [95% CI, 0.602‐0.630], and 0.270 [95% CI, 0.260‐0.279] for PCa, NSCLC, and BCa compared to uninsured patients, respectively. Private insurance provided the most significant benefit to non‐Hispanic White PCa patients with 81% reduction in odds of metastatic presentation and conferred the least benefit to African‐American NSCLC patients at 30.4% reduction in odds of metastatic presentation. Conclusions: Insurance status provided the single most protective effect against metastatic presentation. This benefit varied for minorities despite similar insurance. Reducing metastatic disease presentation rates requires addressing social barriers to care independent of insurance. Abstract : Ethnicity and insurance status have been shown to impact odds of presenting with metastatic cancer, however the interaction of these two predictors is not well understood. In this national‐level analysis, we found that insurance status provided the single most protective effect against metastatic presentation. This benefit varied for minorities despite similar insurance.